Phenotypic analysis of the pediatric immune response to SARS‐CoV‐2 by flow cytometry. Issue 3 (10th January 2022) - Sibbertsen, Freya; Glau, Laura; Paul, Kevin; Mir, Thomas S.; Gersting, Søren W.; Tolosa, Eva; Dunay, Gabor A.
Abstract: Pediatric SARS‐CoV‐2 infection is often mild or asymptomatic and the immune responses of children are understudied compared to adults. Here, we present and evaluate the performance of a two‐panel (16‐ and 17 parameter) flow cytometry‐based approach for immune phenotypic analysis of cryopreserved PBMC samples from children after SARS‐CoV‐2 infection. The panels were optimized based on previous SARS‐CoV‐2 related studies for the pediatric immune system. PBMC samples from seven SARS‐CoV‐2 seropositive children from early 2020 and five age‐matched healthy controls were stained for analysis of T‐cells (panel T), B and innate immune cells (panel B). Performance of the panels was evaluated in two parallel approaches, namely classical manual gating of known subpopulations and unbiased clustering using the R‐based algorithm PhenoGraph. Using manual gating we clearly identified 14 predefined subpopulations of interest for panel T and 19 populations in panel B in low‐volume pediatric samples. PhenoGraph found 18 clusters within the T‐cell panel and 21 clusters within the innate and B‐cell panel that could be unmistakably annotated. Combining the data of the two panels and analysis approaches, we found expected differentially abundant clusters in SARS‐CoV‐2 seropositive children compared to healthy controls, underscoring the value of these two panels for the analysis of immune response to SARS‐CoV‐2. We established a two‐panel flow cytometry approach that can be used with limited amounts of cryopreserved pediatric samples. Our workflow allowed for a rapid, comprehensive, and robust pediatric immune phenotyping with comparable performance in manual gating and unbiased clustering. These panels may be adapted for large multi‐center cohort studies to investigate the pediatric immune response to emerging virus variants in the ongoing and future pandemics.